A Case Study of Exploring Pedagogical Practices Applied to Enhance Critical Thinking and Oral Commmunication Skills - Lia Agustina; Farida Ulfa; Anik Khusna; Rita Darmayanti (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
The pedagogical practices mostly applied in the English for Specific Purposes (ESP) contexts include case-based learning (CBL). The CBL directs lecturers to teach their students about real decision-making scenarios. It is interactive learning and includes student-centered learning that shifts the classroom process to improve students’ critical learning and oral communicative skills. Therefore, this study investigates the pedagogical practices predominantly employed in ESP contexts, with a particular focus on case-based learning. CBL encourages lecturers to engage students with real decision-making scenarios, fostering an interactive, student-centered learning environment. This approach aims to enhance students' critical thinking and oral communication skills. Consequently, the research aims to explore how pedagogical practices can be used to improve these skills. To achieve this objective, the researchers conducted classroom action research involving 25 Accounting department students at State Polytechnic, Malang, who were enrolled in ESP courses. Data were collected through questionnaires, interview guidelines, and classroom observations, comprising both qualitative and quantitative data. The qualitative data were analyzed through data condensation, data display, and drawing and verifying conclusions. The findings indicate that students showed significant improvement in both critical thinking and oral communication skills. In terms of critical thinking, students demonstrated the ability to analyze and evaluate arguments presented by their peers, discerning the truthfulness of the information. Regarding speaking skills, students effectively organized and communicated their ideas. These findings suggest that case-based learning is a valuable method for enhancing language skills, including reading, writing, and listening, in addition to speaking and critical thinking. Future studies should consider applying CBL to other aspects of language teaching to further validate its efficacy.